Sociabilidade, cultura e biodiversidade na Beira de Abaetetuba no Pará - Flávio Bezerra Barros (Ciências Sociais Unisinos)
Open markets are important spaces of socialization and cultural manifestation. They present different functions in the life of the contemporary societies, as it offers products and services, for example. The present text focuses the Abaetetuba/Pará ("the edge") market concerning the aspects of the sociability, culture and biodiversity, and the way these factors infl uence the daily life of the local actors. The participant observation and the accomplishment of interviews and informal colloquies were the main methods of collection of data. The "edge", therefore, exerts primordial role in the life of the citizens, serving as a point of reinforcement of the nets of social interaction; co-operating in the process of the local economy establishment; maintaining the culture and offering products and services, particularly those deriving from the Amazonian biodiversity.